Integrating Public Health–Oriented E-Learning Into Graduate Medical Education - Hemans-Henry, Calaine (American Public Health Association, 2012)
Objectives. In fall 2008, the New York City Department of Health and Mental Hygiene collaborated with Albert Einstein College of Medicine residency program directors to assess the effectiveness of an e-learning course on accurate death certificate completion among resident physicians. Methods. We invited postgraduate year 1 and 2 (PGY1 and PGY2) residents (n = 227) to participate and administered a pretest, e-learning module, posttest, and course evaluation to PGY1 residents; PGY2 residents completed a pretest and survey only. Results. In all, 142 residents (63%) participated. The average pretest scores for PGY2 residents (61%) and PGY1 residents (59%) were not significantly different. The PGY1 residents’ average test score increased significantly after taking the e-learning module (59% vs 72%; P < .01). The participants rated course length, delivery method, and utility highly. Conclusions. Results suggest that e-learning can effectively integrate public health–oriented training into clinical residency programs.